Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized for You

we will pick new questions that match your level based on your Timer History

Track Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:

Re: If 6xy = x^2*y + 9y, what is the value of xy? [#permalink]
05 Jun 2013, 04:13

4

This post received KUDOS

The equation in question can be rephrased as follows: x^2 y – 6xy + 9y = 0

y(x^2 –6x+9)=0

y(x–3)^2=0￼

Therefore, one or both of the following must be true: y = 0 or x=3 It follows that the product xy must equal either 0 or 3y. This question can therefore be rephrased “What is y?”

(1) INSUFFICIENT: This equation cannot be manipulated or combined with the original equation to solve directly for x or y. Instead, plug the two possible scenarios from the original equation into the equation from this statement:

If x = 3, then y = 3 + x = 3 + 3 = 6, so xy = (3)(6) = 18. If y = 0, then x = y – 3 = 0 – 3 = -3, so xy = (-3)(0) = 0. Since there are two possible answers, this statement is not sufficient.

(2) SUFFICIENT: If x3 < 0, then x < 0. Therefore, x cannot equal 3, and it follows that y = 0. Therefore, xy = 0.

Ans B

Please someone confirm on the solution, if the approach is correct

_________________

Correct me If I'm wrong !! looking for valuable inputs

Re: If 6xy = x^2*y + 9y, what is the value of xy? [#permalink]
05 Jun 2013, 04:25

2

This post received KUDOS

Expert's post

1

This post was BOOKMARKED

Manhnip wrote:

The equation in question can be rephrased as follows: x^2 y – 6xy + 9y = 0

y(x^2 –6x+9)=0

y(x–3)^2=0￼

Therefore, one or both of the following must be true: y = 0 or x=3 It follows that the product xy must equal either 0 or 3y. This question can therefore be rephrased “What is y?”

(1) INSUFFICIENT: This equation cannot be manipulated or combined with the original equation to solve directly for x or y. Instead, plug the two possible scenarios from the original equation into the equation from this statement:

If x = 3, then y = 3 + x = 3 + 3 = 6, so xy = (3)(6) = 18. If y = 0, then x = y – 3 = 0 – 3 = -3, so xy = (-3)(0) = 0. Since there are two possible answers, this statement is not sufficient.

(2) SUFFICIENT: If x3 < 0, then x < 0. Therefore, x cannot equal 3, and it follows that y = 0. Therefore, xy = 0.

Ans B

Please someone confirm on the solution, if the approach is correct

Yes, that's correct.

If 6xy = x^2y + 9y, what is the value of xy?

6xy=x^2y + 9y --> y(x^2-6x+9)=0 --> y(x-3)^2=0 --> either x=3 or y=0 (or both).

(1) y – x = 3. If y=0 and x=-3, then xy=0 but if x=3 and y=6, then xy=18. Not sufficient.

(2) x^3 < 0 --> x<0 --> x\neq{3}, then y=0 and xy=0. Sufficient.

Re: If 6xy = x^2*y + 9y, what is the value of xy? [#permalink]
19 Jun 2014, 02:10

Hello from the GMAT Club BumpBot!

Thanks to another GMAT Club member, I have just discovered this valuable topic, yet it had no discussion for over a year. I am now bumping it up - doing my job. I think you may find it valuable (esp those replies with Kudos).

Want to see all other topics I dig out? Follow me (click follow button on profile). You will receive a summary of all topics I bump in your profile area as well as via email.

Re: If 6xy = x^2*y + 9y, what is the value of xy? [#permalink]
06 Jul 2014, 06:34

Bunuel wrote:

Manhnip wrote:

The equation in question can be rephrased as follows: x^2 y – 6xy + 9y = 0

y(x^2 –6x+9)=0

y(x–3)^2=0￼

Therefore, one or both of the following must be true: y = 0 or x=3 It follows that the product xy must equal either 0 or 3y. This question can therefore be rephrased “What is y?”

(1) INSUFFICIENT: This equation cannot be manipulated or combined with the original equation to solve directly for x or y. Instead, plug the two possible scenarios from the original equation into the equation from this statement:

If x = 3, then y = 3 + x = 3 + 3 = 6, so xy = (3)(6) = 18. If y = 0, then x = y – 3 = 0 – 3 = -3, so xy = (-3)(0) = 0. Since there are two possible answers, this statement is not sufficient.

(2) SUFFICIENT: If x3 < 0, then x < 0. Therefore, x cannot equal 3, and it follows that y = 0. Therefore, xy = 0.

Ans B

Please someone confirm on the solution, if the approach is correct

Yes, that's correct.

If 6xy = x^2y + 9y, what is the value of xy?

6xy=x^2y + 9y --> y(x^2-6x+9)=0 --> y(x-3)^2=0 --> either x=3 or y=0 (or both).

(1) y – x = 3. If y=0 and x=-3, then xy=0 but if x=3 and y=6, then xy=18. Not sufficient.

(2) x^3 < 0 --> x<0 --> x\neq{3}, then y=0 and xy=0. Sufficient.

Aaah this formatting.. I read the stem as x^(2y) and was totally stuck. Can this ambiguity in notation come in actual test ? I would have expected a bracket or at the least correct ordering like 6xy = yx^2

Re: If 6xy = x^2*y + 9y, what is the value of xy? [#permalink]
06 Jul 2014, 10:12

Expert's post

himanshujovi wrote:

Bunuel wrote:

Manhnip wrote:

The equation in question can be rephrased as follows: x^2 y – 6xy + 9y = 0

y(x^2 –6x+9)=0

y(x–3)^2=0￼

Therefore, one or both of the following must be true: y = 0 or x=3 It follows that the product xy must equal either 0 or 3y. This question can therefore be rephrased “What is y?”

(1) INSUFFICIENT: This equation cannot be manipulated or combined with the original equation to solve directly for x or y. Instead, plug the two possible scenarios from the original equation into the equation from this statement:

If x = 3, then y = 3 + x = 3 + 3 = 6, so xy = (3)(6) = 18. If y = 0, then x = y – 3 = 0 – 3 = -3, so xy = (-3)(0) = 0. Since there are two possible answers, this statement is not sufficient.

(2) SUFFICIENT: If x3 < 0, then x < 0. Therefore, x cannot equal 3, and it follows that y = 0. Therefore, xy = 0.

Ans B

Please someone confirm on the solution, if the approach is correct

Yes, that's correct.

If 6xy = x^2y + 9y, what is the value of xy?

6xy=x^2y + 9y --> y(x^2-6x+9)=0 --> y(x-3)^2=0 --> either x=3 or y=0 (or both).

(1) y – x = 3. If y=0 and x=-3, then xy=0 but if x=3 and y=6, then xy=18. Not sufficient.

(2) x^3 < 0 --> x<0 --> x\neq{3}, then y=0 and xy=0. Sufficient.

Aaah this formatting.. I read the stem as x^(2y) and was totally stuck. Can this ambiguity in notation come in actual test ? I would have expected a bracket or at the least correct ordering like 6xy = yx^2

Edited the original post to avoid such confusions in future.

By the way x^2y means x^2*y. If it were x^{2y} it would be written x^(2y). But don't worry on the actual test the formatting will be clearer.

Re: If 6xy = x^2*y + 9y, what is the value of xy? [#permalink]
06 Jul 2014, 20:23

Bunnuel,

Why is it wrong to divide the original equation by y? Since dividing the equation by y gives you x^2-6x+9=0 which gives you x=3, then statement 1 is sufficient to give you the value of y and therefore give you the value of xy as 18.

Statement 2 is not consistent with the original equation as it shows x^3<0 which is not possible (x=3, so 3^3=27) and is therefore insufficient. Therefore, answer should be A.

Or is it that only because statement 2 is inconsistent with the original equation and therefore we need to try a different approach?

Re: If 6xy = x^2*y + 9y, what is the value of xy? [#permalink]
07 Jul 2014, 00:06

1

This post received KUDOS

Expert's post

ravih wrote:

Bunnuel,

Why is it wrong to divide the original equation by y? Since dividing the equation by y gives you x^2-6x+9=0 which gives you x=3, then statement 1 is sufficient to give you the value of y and therefore give you the value of xy as 18.

Statement 2 is not consistent with the original equation as it shows x^3<0 which is not possible (x=3, so 3^3=27) and is therefore insufficient. Therefore, answer should be A.

Or is it that only because statement 2 is inconsistent with the original equation and therefore we need to try a different approach?

If you divide (reduce) 6xy = x^2*y + 9y by y, you assume, with no ground for it, that y does not equal to zero thus exclude a possible solution (notice that both y = 0 AND x = 3 satisfy the equation).

Never reduce equation by variable (or expression with variable), if you are not certain that variable (or expression with variable) doesn't equal to zero. We can not divide by zero.